Utilization of Vegetable Waste to Produce Local Microorganisms by Gapoktan Patri in Selopamioro Village, Bantul - Meyzita, Chania; Euriga, Epsi; Fauziah, Nicky Oktav (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to examine the implementation and evaluation of an agricultural extension program based on the utilization of vegetable waste to produce local microorganisms by the Farmers Group Association (Gapoktan Patri) in Selopamioro Village, Bantul. The research was conducted through an extension activity using lecture and demonstration methods, targeting 20 Patri Farmers Group Association (Gapoktan) members. The analysis showed that the extension program improved farmers’ knowledge, attitudes, and skills, as measured by pre-test and post-test questionnaires. Knowledge increased by 6%, attitudes by 3.14%, and skills by 67.5%. Furthermore, the evaluation of the extension program revealed that its effectiveness was 6% for knowledge (less effective), 3% for attitudes (less effective), and 67% for skills (effective). Meanwhile, the effectiveness of behavior change was 24% for knowledge (less effective), 21% for attitudes (less effective), and 89% for skills (effective). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 4: Quality EducationSDG 13: Climate Action